Description of Gestational Mellitus Diabetes in the General Hospital Dr. Zainoel Abidin Banda Aceh in 2018 - Cut Meurah Yeni; Aldilo Talima; Hijdrian Milzam (Budapest International Research and Critics University, 2020)
Gestasional diabetes mellitus (GDM) is a glucose intolerance of variable severity with onset or first recognition during pregnancy. This is a silence occurred disease by the patient so it made much of morbidity for baby and the mother. Purpose of the research is to found the prevalence of GDM in RSUDZA and how was the delivery outcome in 2018. This is a descriptive research which use medical record as a secondary data. Sample of the research is all of pregnant woman who diagnosed with GDM and got treatment at RSUDZA in 2018. From the research we got from 2538 pregnant woman there are 55 of them was diagnosed with GDM. 15 of them (27,3%) had a baby with birthweight >4000gr, and 6 of them (10,9%) had a baby with birthweight <2500gr.